2009
DOI: 10.1111/j.1439-0531.2009.01507.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cooling Rate to 5°C, Straw Size and Farm on Fertilizing Ability of Cryopreserved Rabbit Sperm

Abstract: High fertility and prolificacy in rabbits are currently only achieved using fresh sperm. This study was conducted to determine if the cooling rate to 5 °C, the straw size and the farm where artificial inseminations are performed have an impact on the fertilizing ability of rabbit sperm cryopreserved with an extender containing dimethyl sulphoxide (DMSO; 1.75 m) and sucrose (0.05 m). Slow cooling to 5 °C improved neither fertility rate (58 vs 56% kindling rate for fast and slow cooling, respectively) nor prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
3
14
0
2
Order By: Relevance
“…When using this diluent and 0.5-mL straws, the medium freezing rate (À408C min À1 ) provided a better quality after thawing, similar to that obtained with the control protocol. The freezing rate obtained for the 0.5-mL straws using the freezing diluent and protocol described in this study (straws suspended 5 cm above the liquid nitrogen level) was recently published (Mocé et al 2010). According to those results, the straws are frozen at an approximate freezing rate of À548C min À1 , which is intermediate between the medium and the fast protocols of the programmable freezer.…”
Section: Discussionmentioning
confidence: 96%
“…When using this diluent and 0.5-mL straws, the medium freezing rate (À408C min À1 ) provided a better quality after thawing, similar to that obtained with the control protocol. The freezing rate obtained for the 0.5-mL straws using the freezing diluent and protocol described in this study (straws suspended 5 cm above the liquid nitrogen level) was recently published (Mocé et al 2010). According to those results, the straws are frozen at an approximate freezing rate of À548C min À1 , which is intermediate between the medium and the fast protocols of the programmable freezer.…”
Section: Discussionmentioning
confidence: 96%
“…Effect of equilibration time at 5 C on the in vitro quality parameters of cryopreserved rabbit sperm For this experiment, nine different pooled ejaculate samples were split into six aliquots. Each aliquot was diluted (1:1; v:v) with the freezing diluent (Tris-citric acidglucose with 3.5 M of DMSO and 0.1 M of sucrose [6]) at room temperature (22 C), packaged into 0.5 mL plastic straws (Minitüb Ibérica S.L., Tarragona, Spain), which were sealed with polyvinyl alcohol (IMV Technologies, L'Aigle, France), and each group of straws placed into a 5 C chamber. Straws were removed from the chamber at 0, 10, 15, 20, 30, and 45 minutes (control; [9]) and frozen in static nitrogen vapor (5 cm above the liquid nitrogen) for 10 minutes, after which they were plunged into liquid nitrogen for storage [9].…”
Section: Experimental Designmentioning
confidence: 99%
“…The ejaculates were collected using an artificial vagina and prepared as described by Mocé et al [6]. Eighty-nine percent of the ejaculates collected fulfilled the quality parameters and were used for the experiments.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…When AI with frozen-thawed sperm was performed, the possible losses of fertility were compensated by increasing the number of spermatozoa in the insemination doses (Salomon and Maxwell, 2000). For instance, despite the reduction in the number of motile and non-reacted acrosome sperm, the protocol used in the present study reported successful fertility rates, as shown in previous studies Mocé et al, 2010).…”
Section: Discussionsupporting
confidence: 82%